My Dream, My Rules: Can Lucid Dreaming Treat Nightmares? - de Macêdo, Tainá Carla Freitas; Ferreira, Glescikelly Herminia; de Almondes, Katie Moraes; Kirov, Roumen; Mota-Rolim, Sérgio Arthuro (Frontiers in Psychology, 2019)
Nightmares are defined as repeated occurrences of extremely dysphoric and well-remembered dreams that usually involve subjective threats to survival, security, or physical integrity. Generally, they occur during rapid eye movement sleep (REMS) and lead to awakenings with distress and insufficient overnight sleep. Nightmares may occur spontaneously (idiopathic) or as recurrent nightmares. Recurrent nightmares cause significant distress and impairment in occupational and social functioning, as have been commonly observed in post-traumatic stress disorder, depression and anxiety. By contrast, during lucid dreaming (LD), subjects get insight they are dreaming and may even control the content of their dreams. These features may open a way to help those who suffer from nightmare disorder through re-significations of the dream scene, i.e., knowing that they are dreaming and having control over their dream content. Thus, lucid dreamers might be able to render nightmares normal dreams, thereby assuring a restoring sleep. The aim of the present study is to review the existing literature of the use of LD as an auxiliary tool for treatment of nightmares. We conducted a careful literature search for eligible studies on the use of LD treatment for nightmares. We observed that whereas LD may be a feasible aid in the treatment of patients with nightmares through minimizing their frequency, intensity and psychological distress, the available literature is still scarce and does not provide consistent results. We conclude therefore that more research is clearly warranted for a better estimation of the effective conductance and therapeutic outcome of LD treatment in clinical practice.